Holistic Management with Family Doctor Approach in a 65-Year-Old Woman With Allergi Contact Dermatitis - Istiqomah, Dinni; Utama, Winda Trijayanthi (CV. Jasa Sukses Abadi, 2025)
Allergic contact dermatitis is a skin inflammation caused by exposure to antigens that causes a type IV hypersensitivity reaction and can be experienced by everyone from all ages, races, and genders. The definitive treatment of the disease is to find and avoid the allergen that causes dermatitis. This is a case report study. Data were obtained from anamnesis, physical examination, and patient’s medical records. Mrs. P, 65 years old, came to the Kebon Jahe Community Health Center with complaints of red spots appearing with itching between the fingers of the patient’s right hand since 7 days ago since patient was wearing a metal ring that the patient had used for the first time. The patient was diagnosed with allergic dermatitis based on the history and physical examination. Non-medical and medical interventions were carried out on patients and their families with education regarding the patient’s illness during three home visits. Holistic management with a family doctor approach has been carried out for Mrs. P, 65 years old with allergic contact dermatitis, which is adjusted based on initial holistic diagnostics.